2021
DOI: 10.1002/tal.1907
|View full text |Cite
|
Sign up to set email alerts
|

A metaheuristic‐based optimum tuning approach for tuned liquid dampers for structures

Abstract: This study focuses on the optimization of tuned liquid dampers (TLDs) by using metaheuristic methods using a natural phenomenon as inspiration. Unlike tuned mass dampers (TMDs), TLDs consist of two parts of bodies that contain the passive liquid that is stationary and the active part of the liquid that involves in sloshing. To optimize the amount of optimum active and passive liquids by finding the best dimensional properties of the liquid tank, a two-degree-of-freedom (DOF) model was used as TLD in the dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The density of the liquid, or its kinematic viscosity, affects the damping performance, and, thus, the sloshing. When evaluated in terms of the characteristic features of the design of TLDs, there are studies in which the use of water, and mixtures including water, as the liquid, has shown good results in terms of performance in various vibration control, easy accessibility, and cost [1,2]. Another feature that affects damping is the geometrical characteristics of the damper tank.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The density of the liquid, or its kinematic viscosity, affects the damping performance, and, thus, the sloshing. When evaluated in terms of the characteristic features of the design of TLDs, there are studies in which the use of water, and mixtures including water, as the liquid, has shown good results in terms of performance in various vibration control, easy accessibility, and cost [1,2]. Another feature that affects damping is the geometrical characteristics of the damper tank.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the harmony search algorithm on design optimization has been supported by various studies [15][16][17][18][19][20][21]. In recent years, it has become a preferred algorithm in damper optimization by being applied in the design of mass and liquid dampers [2,22,23]. The harmony search algorithm includes design factors such as memory consideration ratio (HMCR) and fret width (FW).…”
Section: Introductionmentioning
confidence: 99%
“…Nigdeli and Alhan [46] optimized the parameters of the seismic isolation system through the harmony search algorithm. Ocak et al [47] optimized TLDs via metaheuristic methods, including the harmony search algorithm. Ulusoy et al [48] used the harmony search algorithm to investigate the PID parameters of a multistorey structure incorporating active tendon control systems.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the design of tuned liquid damping devices has been optimized using algorithms such as genetic algorithm (GA), particle swarm optimization (PSO), harmony search algorithm (HS), flower pollination algorithm (FPA), artificial bee colony algorithm (ABC), teaching learning-based optimization algorithm (TLBO), and Jaya algorithm (JA). 16,[40][41][42][43][44][45] The JA is a metaheuristic algorithm developed by Rao. 46 It is an algorithm frequently used in various civil engineering problems because it consists of a simple and understandable single phase, the optimization process is fast, and so forth.…”
mentioning
confidence: 99%
“…52 Ocak et al used metaheuristic algorithms in the seismic control of a single-story structure, optimization of TLD parameters, and obtained the optimum TLD parameters in minimizing the structure displacement with the JA. 45 In this study, two single-story structure models of steel and reinforced concrete with different natural damping were optimized for the natural periods of 0.5 and 1 s at different structure-TLD mass ratios, and earthquake analyses were performed. Single-story structure models were exposed to earthquake records named FEMA P-695 far-fault records in earthquake simulation created by Matlab Simulink, and TLD parameters were optimized with JA to minimize structure displacement.…”
mentioning
confidence: 99%